1998
DOI: 10.1161/01.cir.97.22.2252
|View full text |Cite
|
Sign up to set email alerts
|

Application of Serial In Vivo Magnetic Resonance Imaging to Evaluate the Efficacy of Endothelin Receptor Antagonist SB 217242 in the Rat Carotid Artery Model of Neointima Formation

Abstract: Serial MRI provides the opportunity to assess the progression of vascular lumen volume in vivo after balloon angioplasty. MRI measurements can, in conjunction with in vitro histologic measurements, contribute to the understanding of the actions of pharmacologic agents in experimental models of neointima formation. With the use of serial MRI and histologic measurements, it is demonstrated that protection from both lumen volume reduction and neointima formation is obtained in this model by use of a potent, nonpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Considering that the role of the endothelin receptor subtypes in the formation of intimal thickening still requires further clarification (Azuma et al 1994), a selective ET A receptor antagonist, ABT 147627, significantly reduced neointimal hyperplasia forming over porcine coronary-stented injuries (McKenna et al 1998). Similarly, SB 217242, a nonpeptide ET A /ET B receptor antagonist, has been shown to attenuate neointima formation in the rat carotid artery balloon angioplasty model (Chandra et al 1998). Although TAK-044 has been accepted as a nonselective ET A /ET B receptor antagonist, receptor-binding experiments revealed that TAK-044 has the characteristics of an ET A -preferring antagonist (Masuda et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the role of the endothelin receptor subtypes in the formation of intimal thickening still requires further clarification (Azuma et al 1994), a selective ET A receptor antagonist, ABT 147627, significantly reduced neointimal hyperplasia forming over porcine coronary-stented injuries (McKenna et al 1998). Similarly, SB 217242, a nonpeptide ET A /ET B receptor antagonist, has been shown to attenuate neointima formation in the rat carotid artery balloon angioplasty model (Chandra et al 1998). Although TAK-044 has been accepted as a nonselective ET A /ET B receptor antagonist, receptor-binding experiments revealed that TAK-044 has the characteristics of an ET A -preferring antagonist (Masuda et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…MRI also failed to detect lesions induced by a silastic collar around rabbit carotid arteries because of insufficient resolution. 22 Most studies in rats after balloon angioplasty [23][24][25] report changes in lumen volume without direct plaque visualization. Using surgically implanted coils, only Arnder et al 26 and Summers et al 27 detected plaque in vivo in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…Ohlstein et al [68] and Chandra et al [69] performed in vivo (at 4.7T) and ex vivo (at 9.4T) carotid artery imaging in rats. In these ex vivo studies, the various layers of the arterial wall were clearly defined.…”
Section: Techniques For Assessing Cardiac Physiologymentioning
confidence: 99%
“…In rats, the common carotid artery is often used to create endothelial injury due to its accessibility and size [100]. Assessment of injury and disease progression in this model have traditionally relied on histopathological analysis with cross-sectional slides [101]; increasingly, standard MRI and MRA techniques as well as the more novel MR microscopy and contrast agents are being used to assess the vessel wall and quantify the degree of restenosis in addition to histology [68, 69, 102, 103]. …”
Section: Experimental Animal Models Of Cardiovascular Diseasementioning
confidence: 99%